PLANNING OF TRANSPORTATION OF RHEOLOGICAL COMPLEX OILS FROM VARIOUS FIELDS THROUGH AN EXTENSIVE PIPELINE SYSTEM, TAKING INTO ACCOUNT ENSURING THE SPECIFIED QUALITY OF THE DELIVERED OIL - Valeev, Anvar; Tashbulatov, Radmir; Nurmukhamedov, Chingiz (Journal of Applied Engineering Science, 2024)
The article discusses the problem of operating an oil pipeline system in the presence of a significant number of suppliers of rheologically complex oils with different sulfur content and a large number of oil consumers with different requirements for oil quality in terms of sulfur and other parameters. The problem of determining optimal cargo flows in such a system is discussed. A method is proposed for determining optimal cargo flows in a branched oil pipeline system, providing a global optimum in terms of minimizing energy costs for pumping. The article provides an algorithm for implementing the method using a conditional example.
Keywords: oil, oil pipeline system, rheologically complex oil, oil quality by sulfur, viscosity, dynamic programming, algorithmic complexity, optimization of cargo flows